Experimental thermal analysis and modelling of single point lathe cutting tools without cooling effect - Agarwal, A.; Letsatsi, M.T; Seretse, O.M.; Marumo, R. (International Journal of Engineering and Technology, 2018)
This study investigated the use of tungsten carbide tool and high speed steel (HSS) tool when machining aluminum and mild steel. The parameters such as feed and speed of rotation were varied in order to observe their effect on machining operation. The experiments were performed without a coolant. FLIR thermo Cam P60 and Infra-Red Camera were used to record the observations. The highest temperature were recorded when feed rate was 2 mm. A comparison of experiments shows that HSS tooling produced high temperatures when machining mild steel. At 625 rev/min HSS failed when cutting mild steel at 2 mm feed rate. It was generally observed that temperatures generated between a tool and work piece is a function of feed rate, speed of rotation and tool material. These observations can aid the selection of a tool before a machining operation.